Konstruktywistyczna perspektywa wczesnej edukacji przyrodniczej - Renata Michalak (Problemy Wczesnej Edukacji)
This article reflects on how to use children’s natural curiosity in early science education and make learning a meaningful, joyful and useful experience for them. Therefore, an attempt was made to show the essence of the constructivist model of teaching natural science to the youngest students by referring to the strategy of teaching through inquiry and outdoor education.